Little diva [compact disc, unabridged] - LaChanze (Feiwel and Friends, 2010)
Nena wants to be a Diva, with a capital D, just like her mommy, who's a star on Broadway. So she learns all she can about singing and dancing when she is at the theater and trains day and night to make her dreams come true.